Moisture dependent physico-mechanical and aerodynamic properties of roselle calyxes (Hibiscus sabdariffa) - Akharume, Felix U; Aregbesola, Omotayo A (Journal of Postharvest Technology, 2019)
The design of compatible harvesting and post-processing equipment as well processing techniques require information on the physical,  mechanical and aerodynamic properties of agricultural materials. Therefore, this study focused on determination of some moisture dependent  mechanical and aerodynamic properties of a dark red variety of roselle calyxes. Experiments were conducted to measure some physico mechanical and aerodynamic properties of the roselle calyxes (such as dimensions, porosity, true and bulk density, peak rupture force, tensile  strength, stiffness, modulus of elasticity, toughness, terminal velocity and drag coefficient) at three different moisture contents (14.40, 18.00  and 23.87%, w.b). Results showed that length, width, and thickness of the calyxes ranged from 41.10 - 53.10 mm, 20.60 – 24.1mm, and 1.11  – 1.32mm, respectively. Changes in bulk density was negligible as the calyx moisture content was increased from 14.4 to 23.87 % while  increment with increased moisture content was recorded for values of surface area, true density, and porosity. The Peak rupture force,  tensile strength, stiffness, modulus of elasticity and toughness of the calyxes ranged from 5.30 – 8.47 N; 442 – 692kNm-2; 4.06 – 4.31kNm-1;  13.47 - 14.78 MNm-2, 0.0035 - 0.0112 J, respectively. Terminal velocity (TV) of the calyxes was between 2.78 – 3.22 ms-1 and the values for  drag coefficient ranged from 1.60 x 10-3– 2.9 x 10-3.
Keywords: Aerodynamic properties; mechanical properties; physical properties; roselle calyxes